PEMANFAATAN EKSTRAK KULIT BUAH NAGA MERAH BERDASARKAN PENGARUH UKURAN PARTIKEL SEBAGAI INDIKATOR ASAM-BASAPADA PROSES TITRASI - Ade Era Febriani; Noorma Kurnyawaty; Firman Firman (Politeknik Negeri Samarinda, 2022)
Dragon fruit skin contains flavonoid compounds, one of which is anthocyanin. This anthocyanin can change color as the pH value changes so it can be applied as an acid-base titration indicator. The purpose of this research is to utilize red dragon fruit skin extract (Hylocereus polyrhizus) as an acid-base indicator in the titration process based on the influence of particle size (3.00 × 3.00 × 1.00) cm; (-14+18); (-18+20); (-20+70); (-70+100); (-100+120) mesh. The extract was obtained by maceration extraction for 24 hours with 96% ethanol solvent: 10% citric acid. The results of determining the color change trajectory were obtained when the acidic condition was light brown and when the alkaline condition was bright yellow. The highest result was obtained at particle size of -14 + 18 mesh with a rendement of 30.42%. The extract was tested as an acid-base titration indicator with a pH range of 8.3–10.0 for the pp indicator as a comparison, while methyl orange was used as a comparison with a pH of 3.1 – 4.4. So that this red dragon fruit peel extract can be used as an indicator in acid-base titration. Keywords: Acid-base titration, particle size, red dragon fruit peel